TINDAK TUTUR ILOKUSI DENGAN MENGGUNAKAN KATA UZAI PADA DRAMA YANKEE-KUN TO MEGANE-CHAN - Wirda Syafirna; Zuli Laili Isnaini; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstarct: This study described the types and contexts of using illocutionary act by using uzai that used to curse in the Drama of Yankee-kun to Megane-chan. The use of a speech has a purpose not only to express something, but also to do something or action. It is in pragmatic known as the illocutionary act. Drama of Yankee-kun to Megane-chan by Miki Yoshikawa originally in the form of a manga, then made in drama, and aired on April 23, 2010 until June 25, 2010 on Japanese TV station TBS. The theory used in this study is the types of illocutionary acts by Searle (1979) and theory of usage context by using theory of Dell Hymes (1964) with qualitative descriptive approach. The result of this research are (1) found speech that using word